REVIEWS OF THE SCIENTIFIC LITERATURE: TYPES, METHODS AND APPLICATIONS IN NURSING - Luís Manuel Mota De Sousa; Cristiana Furtado Firmino; Cristina Maria Alves Marques-Vieira; Sandy Silva Pedro Severino; Helena Castelão Figueira Carlos Pestana (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Introduction: The interest of nursing in the methodology of systematic review of the literature has been increasing, since it constitutes a method that allows a practice based on scientific evidence with scientific rigor. Objective: To characterize the different types of literature review and to describe the main steps of a systematic review of the literature Material and methods: Narrative review of the literature. Database search on the following platforms: Google Academic, Scientific Electronic Library Online (SciELO), EBSCO Host, and Virtual Health Library (VHL). Keywords: meta-analysis; evidence-based medicine; review literature as topic; methodology, in the English and Portuguese languages. Results: fourteen types of reviews were described and analyzed according to the type of research, evaluation of the methodological quality of the articles included, synthesis of the information collected and global analysis of the data. The advantages and disadvantages of each type and the main steps of a systematic review of the literature were presented. Conclusions: A systematic review of the literature is the foundation for evidence-based practice, since it aggregates a large amount of information in a single study.